Why Open Innovation is Easier Said Than Done: An Organizational Identity Perspective - Maral Mahdad; Chiara E. De Marco; Andrea Piccaluga; Alberto Di Minin (Journal of Innovation Management, 2020)
In this article, we explore and interpret organizational identity transformation associated with open innovation strategy of the largest telecommunication company in Italy, Telecom Italia (TIM). When TIM established eight joint laboratories within five major Italian universities to benefit from opening its business model, it transferred some of the R&D employees to the new laboratories to work with the university scientists. This organizational transformation created underexplored conditions for R&D employees engaged in the open innovation activities of the firm. Our interpretive phenomenological analysis (IPA) answers the question of “How do R&D employees experience organizational identity change in the process of open innovation?”. We based our analysis on interpreting lived experiences of 14 employees. Studying the phenomena of organizational identity change during the process of open innovation implementation suggests the following: (1) The process of open innovation through mobility of skilled R&D employees triggers organizational identity ambiguity and change, (2) Organizational identity ambiguity phase in the process of open innovation can be shortened by the support of parent company and managerial skills highlighting sensemaking mechanisms, (3) Constructing a shared organizational identity with university members involved in this process is an undeniable element of OI success for this strategy. We contribute to the literature by establishing linkages among organizational identity and open innovation and by building on recent works on the role of individuals within open innovation ecosystem. Our qualitative analysis draws on a conceptual framework for open innovation and organizational identity transformation.